Peranan Lembaga Litbang dalam Rangka Mendorong Meningkatkan Ketahanan Pangan - Murwanto, Tri Agus (Jurnal Aplikasi Manajemen, 2008)
Endure of food is part is very important for nationality, so, the right ood should be an attention and it is basic for nationality of nationationality of endurance. Without enugh meal and high nutrient, the next generation will be paralyzed slowly. In the framework to example to anticipate that case reseach and development institute must practice with all side, for example goverment, includeing local goverment, industry, cooperation, and others to solve the problems that they face like the problem with process technology, prototype and the other food good technology. The oncep is to support and endurance.